Evaluation programs for Italian teams preparing the Paralympic Games - Bernardi, M. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: A collaboration among Italian Paralympic Committee (CIP), National Institute of Sports Medicine and Science (ISS - of the Italian Olympic National Committee), School of Specialty in Sports Medicine (SSSM) - Department of Human Physiology and Pharmacology of the University of Rome "La Sapienza" and Inter-Universities Centre of Research in Bioengineering and Motor Sciences (Ce.Bi.S.M.), Rovereto (Trento) has made possible a new and innovative comprehensive and multidisciplinary evaluation program for the Italian Nordic and Alpine Paralympic Skiers (INAPS) selected as possible participant of Turin 2006 Winter Games. Within a research project sponsored by CIP, the Ce.Bi.S.M., directed by Professor Federico Schena, with a specific support given by the Municipality of Rovereto, which offers complete hospitality to the athletes (board and lodging), provides, since the beginning of 2005 (Pre-Paralympic Test Events in Pragelato - Turin) and up to the next Paralympic Games, human and instrumental resources to carry out sophisticated and comprehensive physiologic evaluations of all INAPS selected by the Alpine and Nordic head coaches in their teams. This research project, aimed at improving the athletic characteristics of the INAPS to improve their specific performance, is based on field and laboratory measurements taken since 1997 within a collaboration among the Italian Federation of Sports for Disabled (now CIP), ISS and SSSM. In this study energy cost and metabolic and cardiovascular workloads of cross-country sit-skiing race was assessed in top level Paralympic athletes with different levels and types of locomotor disabilities. These data were compared with athletes` physiological profiles, assessed in terms of aerobic and anaerobic fitness, to study the energy sources of the three typical races (5, 10 and 15 km) and to improve performance with specific training. In the present study we want to test the hypotheses that a high aerobic power is a fundamental requisite of a successful cross-country sit-skier (CCSS) and that a high anaerobic power allow the CCSS to win a race. A second aim of the current part of this research is the assessment of specific methods (ergometers and protocols) to both evaluate CCSSs in the most specific way and, possibly, train their maximal aerobic and anaerobic power. Methods: Athletes involved in the program have been tested in SSSM, ISS and Ce.Bi.S.M. laboratories using an arm cranking ergometer (ACE- ER800, Cosmed, Italy) to assess, through a breath-by-breath metabolimeter (Quark b2, Cosmed, Italy) and a blood lactate analyser (Lactate-Pro, Arkray, Inc., Japan), maximum aerobic power (oxygen consumption peak -VO2peak- and anaerobic threshold), during a continuous multistage incremental maximal exercise test, and maximal anaerobic capacity, during an all-out exercise test based on the VO2peak measurement. In Ce.Bi.S.M. based on the experience related to able-bodied Nordic skiers and with the collaboration of CIP, an instrumented "Upper Body Nordic Ski-Simulator" ergometer (UBNSE), consisting of ropes connected to separated electric motors, has been developed and adapted to measure CCSS`s force and velocity applied by each upper limb when pulling during a movement simulating cross-country sit-skiing races at different exercise intensities. Four 10 second long maximal tests, to assess maximal strength at different velocities during pulling, and a 50 second long all-out test, to assess maximal work capacity, average power and decay of strength and power, have been devised and carried out in 3 consecutive test sessions. Kinematics of the arm movements have be evaluated by using passive marker on joints after calculation of an averaged cycle obtained by optoelectronic computerised system (Proreflex, Qualysis, Sweden). Athletes` physiological response have been recorded (Quarkb2 or K4b2,Cosmed, Italy and Lactate-Pro, Arkray, Inc., Japan) both during the all-out test and in a test on a treadmill (T300LR, Cosmed, Italy). The latter allow CCSS to simulate crosscountry race conditions skiing with their own Nordic sitting device equipped with ski-rolls. Data obtained through the ACE will be compared with the two specific ergometers. A K4b2 metabolimeter and video recording have been used for "on field measurements". All the laboratory results will be correlated with race and training performances. Results: Race V`O2 was equal to 45±5 ml•kg-1•min-1 in male athletes and to 34±1 ml•kg-1•min-1 in female athletes, averaging 83±3% of their ACE V`O2peak. In both genders mean heart rate was equal to 177±8 beats per minute. In men the mean energy cost, averaging data from the three race events, was equal to 1120 joules per minute and per kilogram of body mass. The contribution of aerobic energy source to the total energy expenditure during race performance is about 91% and the maximum aerobic power strictly correlated with race mean V`O2 (r =0.98, p<0.01). The UBNSE resulted very effective in evaluating appropriately the muscular characteristics of the CCSS. Studies to devise specific protocols to assess V`O2peak and anaerobic threshold and to reproduce cross-country sit-skiing energy cost modulating speeds and slopes of the treadmill are in progress. Preliminary results obtained using the treadmill shows that it can be used to reproduce race conditions and that CCSS seem to reach higher V`O2peak and anaerobic threshold values than with the ACE. Discussion/Conclusion: For the first time INAPS are followed in a routinely manner during their training period proceeding the Winter Games. Coaches and athletic trainers are provided with continuous laboratory results to monitor the effects of the training. Based on the final adjustments of the UBNSE and treadmill test protocols we expect, first, to devise specific evaluation tests to build performance models able to predict race results and to recruit talented individuals, secondly, we expect to set-up new training programs effective in improving performance.